The impact of internal supply chain integration on perceived product quality: A case study of Moulin de Laghouat Spa - Marfoua Moussa; Moulay Lakhdar Abderazzak; Dahou Slimane (Dirassat Journal Economic Issue, 2021)
This study examines the relationship between internal Supply chain integration (ISCI) and Perceived product quality (PPQ) in Moulin de Laghouat company. Inter-functional Coordination (CRD), cooperation (COP), and collaboration (CLB) are introduced as dimensions of the ISCI. In this research, A path model analysis was used to evaluate the model through partial least squares structural equation modeling (PLS-SEM). The analysis of collected data from thirty employees of Moulin de Laghouat company in Algeria was performed using SmartPLS 3. Findings indicate that ISCI and CRD had an impact on PPQ. Simultaneously, both COP and CLB as dimensions of (ISCI) have no significant effect on PPQ. Results show that Moulins de Laghouat should adopt an efficient information system by implementing an ERP system to help different departments coordinating their activities. Moreover, reach a higher level of cooperation and collaboration within ISCI.